A review on composite patch repairs and the most important parameters affecting its efficiency and durability. (January 2021) - Mohammadi, Sirvan; Yousefi, Mohammad; Khazaei, Mahdi
In many industries, when replacement of a part is not possible or economic, the repair is done. One of the best methods for repairing metal and composite parts is using composite patches. Repairing with a composite patch is a widespread field to extend the service life of the cracked components. This technique is more structurally efficient with fewer damages on the structure than others. The bonded patch offers many advantages over a mechanically fastened doubler, which include improved fatigue behavior, reduced corrosion, and easy conformance to complex aerodynamic contours. In this article, advantages of the composite patch and its efficiency and durability are discussed, and the most important parameters (patch and adhesive thickness, patch separation, residual stress, patch length and width, etc.) affecting its performance are studied based on the latest available references.